The effectiveness of self-compassion–based interventions on mental health in adolescent populations: A systematic review - Suci Rahayu; Siti Chodijah; Happy Hayati (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Emotional dysregulation is a major risk factor for varios mental health issues and maladaptive behaviors in adolescents, including self-harm and sacred ideation. Self-compassion (SC) based interventions have been recognized as a promising approach to counter self-criticism and enhance emotional coping skills. Purpose: To evaluate and synthesize the evidence regarding the effectiveness of SC interventions in mental health of adolescents. Method: This systematic review followed the PRISMA 2020 guidelines. Literature searches were conducted in PubMed, ScienceDirect, ProQuest, and Sage Journals for studies published between 2016 and 2025. Eligible studies included adolescents aged 10–19 years receiving self-compassion–based interventions, using RCT or quasi-experimental designs, and reporting mental health outcomes. Screening was conducted using Rayyan after duplicate removal. Methodological quality was assessed using the Cochrane Risk of Bias 2.0 and ROBINS-I tools. Results: All eight studies consistently demonstrated that self-compassion based interventions led to a significant improvement in emotion regulation capacity, encompassing enhanced adaptive cognitive strategies (eg, positive reappraisal) and behavioral aspects of emotional regulation improvement. The interventions prove effective in both group and individual settings. However, most studies presented methodological limitations, including small sample sizes, quasi-experimental design and short follow-up periods. Conclusion: Self-compassion based intervention is an effective and clinically relevant approach for enhancing emotion regulation in adolescents, especially for those in high-risk groups. Further research, ideally large-scale RCTs, with standardized measurements and long-term follow up, is necessary to strengthen the external validity of these findings and support broader program implementation in schools and clinical services.